2003
DOI: 10.2475/ajs.303.6.489
|View full text |Cite
|
Sign up to set email alerts
|

Post-orogenic evolution of the Dabie Shan, eastern China, from (U-Th)/He and fission-track thermochronology

Abstract: The Dabie Shan of eastern China is a ϳ200 kilometers wide mountain range with nearly 2 kilometers of relief and is an archetype of deep ultrahigh-pressure metamorphic rock exhumation. Despite its regional and petrologic importance, little is known about the low-temperature and post-orogenic evolution of the Dabie Shan. Here we present apatite and zircon (U-Th)/He (AHe and ZHe, respectively) and apatite fission-track (AFT) cooling ages from the Dabie Shan that constrain the patterns and history of exhumation ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(160 citation statements)
references
References 52 publications
14
145
1
Order By: Relevance
“…The northeastern extent of the range continues to exhume at ∼ 0.09 km Myr −1 . The time interval from 60-30 Ma shows slower exhumation rates at the front of the range close to the Tan-Lu fault, in agreement with Reiners et al (2003). There is also a decrease in exhumation rate in the eastern region.…”
Section: Exhumation History Of the Dabie Shansupporting
confidence: 74%
See 3 more Smart Citations
“…The northeastern extent of the range continues to exhume at ∼ 0.09 km Myr −1 . The time interval from 60-30 Ma shows slower exhumation rates at the front of the range close to the Tan-Lu fault, in agreement with Reiners et al (2003). There is also a decrease in exhumation rate in the eastern region.…”
Section: Exhumation History Of the Dabie Shansupporting
confidence: 74%
“…We specify a vertical velocity with an exhumation rate of 0.07 km Myr −1 within a rectangular region in the center of the model domain and 0.05 km Myr −1 outside of this rectangle. We predict AHe, AFT and ZHe ages with the Dodson approximation, at the same spatial locations as in Reiners et al (2003). We assign the same measurement errors as in the reported data.…”
Section: Testing Resolution Of the Datamentioning
confidence: 66%
See 2 more Smart Citations
“…The apatite (U-Th)/He thermochronometry is largely significant in studying the late period of basin-mountain uplifting. Bullen [31] studied the cooling rate of the uplifting event in 3-10 Ma in the Kyrgyz Tianshan using apatite (U-Th)/He thermochronometry and Reiners et al [31,32] demonstrated the cooling rate of the uplift event in 23-40 Ma in the Dabie Mountain. Recently, we have used the apatite (U-Th)/He ages first to study the South Tianshan and then revealed the rapid uplift during the Neogene [33].…”
Section: Geological Significance Of Apatite He Closure Temperaturementioning
confidence: 99%